CITY PARK AS ONE OF THE CITY INFRASTRUCTURE SYSTEM (CASE STUDY: TAMAN KAMBANG IWAK PALEMBANG) - Husnul Masyitoh; Agung Budi Sardjono (Jurnal Arsitektur ARCADE, 2023)
Abstract: Palembang or Pempek City is the capital city of South Sumatra Province. Palembang itself is included as the 2nd largest city in Sumatra. With an area of 400 km² and 1.6 million inhabitants in it. Palembang is now classified as a metropolitan city with the fifth density level in Indonesia following Jakarta, Medan, Bandung, Surabaya and is ranked nineteenth in Southeast Asia. It’s recorded in history that it was the capital of the largest Buddhist kingdom, namely the Sriwijaya Kingdom in the ninth century. Palembang has existed since June 16, 683AD and is the oldest city in Indonesia. Along with the development of Palembang  and its rapidly growing population, the government seeks to improve the city's infrastructure system in Palembang  by referring to the economic, social, and cultural aspects of the people of Palembang itself. One of the City Infrastructure Systems that supports community activities is seen in the city park area on Tasik, namely Kambang Iwak Park. For this research, this research was carried out by applying a qualitative descriptive method, which if defined according to Sugiyono (2016) this research method depends on the philosophy of postpositivism which aims to examine natural objects.Keyword: Palembang city; City Infrastructure System; Kambang Iwak ParkAbstrak: Palembang atau kota pempek adalah Ibu Kota Provinsi Sumatera Selatan. Palembang sendiri masuk ke dalam kota terbesar ke-2  se-Sumatera. Dengan luas 400 km² dan 1,6 juta jiwa penduduk  di dalamnya. Palembang sekarang tergolong dalam kota Metropolitan dengan tingkat kepadatan nomor lima se-Indonesia menyusul Jakarta, Medan, Bandung, Surabaya dan menduduki peringkat sembilan belas di Asia Tenggara. Tercatat dalam sejarah pernah menjadi Ibukota Kerajaan Budha terbesar yaitu Kerajaan Sriwijaya pada abad kesembilan. Palembang sudah ada sejak tanggal 16 Juni 683M dan merupakan kota tertua di Indonesia. Seiring perkembangan zaman pembangunan sarana dan prasarana Kota Palembang serta penduduknya semakin pesat, pemerintah berupaya meningkatkan sistem prasarana kota di Kota Palembang dengan beracuan pada ekonomi, sosial, dan budaya masyarakat Palembang sendiri. Salah satu Sistem Prasarana Kota yang menunjang kegiatan masyarakat terlihat pada kawasan taman kota yang ada di jalan Tasik yaitu Taman Kambang Iwak. Untuk penelitian kali ini dilakukan dengan penerapan metode deskriptif kualitatif, yang mana jika didefinisikan menurut Sugiyono (2016) metode penelitian ini tergantung pada filsafat postpositivisme yang bertujuan untuk meneliti objek alamiah.Kata Kunci: Kota Palembang; Sistem Prasarana Kota; Taman Kambang Iwak.